Shock index as a predictor of vasopressor use in patients with sepsis - N., Prashanth V.; ., Sneha (International Journal of Advances in Medicine, 2019)
Background: Sepsis is life-threatening organ dysfunction caused by a dysregulated host response to infection. Sepsis and septic shock are major healthcare problems affecting millions of people around the world each year and killing as many as one in four. The documented incidence of sepsis worldwide is 1.8 million each year with mortality rate of almost 30%. Sepsis is the 10th leading cause of death in the United States. Shock index (SI) is defined as “Heart rate divided by Systolic blood pressure (HR/SBP)”. Normal range is 0.5 to 0.7 in healthy adults. Methods: A Prospective study was conducted between August 2018 to March 2019 comprising of 100 consecutive patients presenting to emergency department and ICU with sepsis. Subjects were identified by having evidence of infection presenting with cardiovascular collapse or organ failure with help of q-SOFA(quick- sepsis related organ failure assessment ) and SOFA scores (sequential organ failure assessment score).Cases with clear alternative diagnosis were excluded. Vital signs were recorded, and Shock index was calculated. Primary outcome, which was use of Vasopressor therapy was analysed. Results : A Total of 100 cases were studied, of which 70 patients were males and 30 females with mean age of 48.5 ±16.2 yrs. Most of the cases were between 35 to 60 years. Patients were classified into 3 categories based on shock index:1. <0.8 (normal, n=16) 2. 0.8 to <1.2 (n=29) 3. >1.2 (n=55). The use of vasopressor therapy within first 24 hours for each group was 18%, 34%, and 78%. This difference was statistically significant (p=<0.05). Conclusion : In patients with sepsis an elevated shock index was indicator of early vasopressor therapy in the first 24hours. It is a simple bedside tool to identify septic patients in need for early vasopressor therapy thereby preventing further clinical deterioration.